KNOWLEDGE OF VOLCANIC DISASTER MANAGEMENT EFFORTS TOWARDS A DISASTER RESILIENT COMMUNITY - Pratama, Hendra; Hattarina, Shofia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Volcanic eruptions are natural disasters that have a wide impact on the affected area. Losses due to volcanic eruptions are not small. By making disaster hazard maps in areas with the potential for volcanic eruptions to occur, the threat of volcanic eruptions can be minimized. Volcanic areas are areas with high availability of resources. Volcanic activity can produce materials that enrich and rejuvenate agricultural soil. The tall bodies of volcanoes are rain collectors, stores and suppliers of groundwater. Volcanic areas are generally dense and densely populated, because the availability of natural resources is the main attraction for the population. Volcanic eruptions, on the other hand, can cause different types of damage. Knowledge about the dangers of volcanoes and their eruptions is needed for the community, this aims as a form of tough resilience in the face of volcanic eruptions. Disaster-aware society has the main goal of reducing the risk of disaster victims, this is because Indonesia is a disaster supermarket which includes geological disasters, climatological disasters, social disasters, technological failure disasters and biological disasters in the form of viruses.